Computation of sediment discharge in rivers: the contributions by Levi and Studenitcnikov revisited. Issue 4 (4th July 2017) - Evangelista, Stefania; Govsha, Jelena; Greco, Massimo; Gjunsburgs, Boriss
ABSTRACT: In the past century, a considerable amount of theoretical and experimental work in all areas of fluvial hydraulics was carried out in Russia. The outcomes of this massive work have been successfully applied in numerous engineering projects in the former Soviet Union. Unfortunately, because of the language barriers and even more due to the geopolitical situation that dominated the last century, the exchange of scientific knowledge between Russia and western countries was greatly impaired. This paper highlights some interesting contributions by the Russian scientists Levi and Studenitcnikov. In particular, Levi's formula for the sediment discharge and Studenitcnikov's formula for the critical velocity are discussed and revisited in light of the Shields approach, currently dominant in the western literature. An application example is given considering prediction of local scour along elliptical guide banks.